Transport for language south of the Sylvian fissure: The routes and history of the main tracts and stations in the ventral language network. (August 2015) - Bajada, Claude J.; Lambon Ralph, Matthew A.; Cloutman, Lauren L.
Abstract: It is now ten years since a 'ventral language pathway' was demonstrated in vivo in the human brain. In the intervening decade, this result has been replicated and expanded to include multiple possible pathways and functions. Despite this considerable level of research interest, age-old debates regarding the origin, course, termination and, indeed, the very existence of the tracts identified still remain. The current review examines four major tracts associated with the ventral 'semantic' language network, with the aim of elucidating and clarifying their structural and functional roles. Historical and modern conceptualisations of the tracts' neuroanatomical origins and terminations will be discussed, and key discrepancies and debates examined. It is argued that much of the controversy regarding the language pathways has resulted from inconsistencies in terminology, and the lack of a white matter 'lingua franca'. Graphical abstract: Representation of the ventral language network showing the four main fibre tracts, their relative routes and cortical terminations.